Saving and Investing “Need to Knows” for Military Families - Barbara O'Neill; Martie Gillen; Kristen Jowers (EDIS, 2024)
This publication is intended for family service providers, Extension agents and specialists, educators, and other professionals in the Military Family Readiness System. It discusses general and military-specific information about saving and investing money. Written by Barbara O’Neill, Martie Gillen, and Kristen Jowers, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2024.